2021
DOI: 10.1016/j.esmoop.2021.100157
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the care of cancer patients in Spain

Abstract: Background Studies evaluating the effects of the COVID-19 pandemic on public healthcare systems are limited, particularly in cancer management. As no such studies have been carried out in Spain, our objective is to describe and quantify the impact of the COVID-19 pandemic on cancer patients in Spanish hospitals during the first wave of the pandemic. Materials and methods This retrospective, multicenter, nationwide study collected information from hospital departments tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 29 publications
(41 reference statements)
3
34
0
2
Order By: Relevance
“…During March and April 2020, the mean number of weekly patients diagnosed with breast, colorectal, lung, pancreatic, or gastric cancer in the US decreased by 46.6% for these 6 types of cancer combined, with the greatest reduction for breast cancer (−51.8%) and the lowest for pancreatic cancer (−24.7%) [10]. Similar findings have been reported in the number of weekly patients diagnosed during the first four months of the pandemic in the Netherlands [6], Italy [11], Germany [12], Spain [19] or Australia [26].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…During March and April 2020, the mean number of weekly patients diagnosed with breast, colorectal, lung, pancreatic, or gastric cancer in the US decreased by 46.6% for these 6 types of cancer combined, with the greatest reduction for breast cancer (−51.8%) and the lowest for pancreatic cancer (−24.7%) [10]. Similar findings have been reported in the number of weekly patients diagnosed during the first four months of the pandemic in the Netherlands [6], Italy [11], Germany [12], Spain [19] or Australia [26].…”
Section: Discussionsupporting
confidence: 72%
“…Between March to July 2020, a decrease in the billing frequency for chemotherapy administration was observed in comparison to 2019, with a maximum of 32% in July, according to Medicare data [8]. Data from a multicenter nationwide study from Spain that collected information from departments treating oncology patients through an electronic questionnaire, reported a decrease of 20.3% in the number of new patients' referrals and of 14.3% in the mean number of patients visiting day hospitals between March-June 2020 compared to March-June 2019 [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, despite there being less activity in the pathology departments during COVID-19 than during 2019, the probability of neoplasia diagnosis during the pandemic has been statistically significantly higher. Although this could be due to changes in the prioritization protocols used by different care services and recommendations by scientific societies and expert groups to minimize the risks [ 20 , 21 , 22 ], in certain types of cancer, it could also be due to the increase in the number of scans due to COVID-19 in patients with undiagnosed cancers. In fact, patients with underlying cancers are probably more vulnerable to SARS-CoV-2 infection and display a worse progression of the disease [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there is a 25% reduction in cancer cases in the March-May 2020 pandemic period in the Netherlands [13]. In Spain, between March and June 2020, the number of new cancer cases decreased by 20.8% compared to 2019, the number of biopsies performed for diagnosis was lower, and the number of visits for patients receiving cancer treatment decreased [14].…”
Section: Discussionmentioning
confidence: 99%